Geostatistical analysis of road traffic accidents for crash reduction site prioritization - Luz, Leonard L.; Blanco, Ariel C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Road traffic injury has become a major public health concern that needs immediate attention and effective interventions. At a global scale, around 1.25 million people are killed annually in road traffic crashes; while the number of people injured is estimated at around 50 million. Accidents in general placed fifth on the leading causes of mortality in the Philippines in 2014. Specifically, the rising trend in road crash casualties in Metro Manila requires an effective method of identifying priority sites for the successful implementation of road crash reduction measures, given the limited amount of resources allotted for road safety. A comprehensive methodology with geostatistical approach using historical road crash data from 2007 to 2016 was developed to determine the priority sites for crash reduction along the three major roads in Metro Manila, namely, EDSA, C5 and Commonwealth Avenue. Network-based kernel density estimation was employed to determine the initial clustering of road traffic crashes while a space-time hot spot analysis was utilized to identify the significant clusters expressed in terms of emerging spatiotemporal hot spot categories. Random Forest with variable importance was then used to rank the identified hot spot categories, and in turn their corresponding locations, based on their influence on the calculated crash rate. Lastly, a hot spot analysis in terms of number of casualties was conducted to supplement the integrated results of the KDE and cluster significance analysis in identifying high priority areas. The identified high-priority areas in EDSA include Timog Avenue intersection until Kamias/Kamuning Road, the vicinity of Quezon Avenue intersection extending to Panay Avenue and Mother Ignacia Avenue, and the area approaching Ortigas Central Business District including intersections with Annapolis Street, P. Santos Avenue (Camp Aguinaldo Gate 3), Connecticut Street, and White Plains Avenue. In C5, high-priority areas are located along Mindanao Avenue section particularly within the vicinity of Floor Center and Wilcon Depot approaching Quirino Highway. In Commonwealth Avenue, high-priority areas include the vicinity of Quezon Memorial Circle extending to Masaya Street, U-turn slots in front of UP-Ayala Land Technohub, sections of Matandang Balara particularly from Luzon Avenue to Zuzuarregui Street, and the vicinity of Fairview General Hospital near Camaro Street intersection. Using Binary Logistic Regression, the contribution of the spatiotemporal and crash-related factors to crash severity was also distinguished in conjunction to identifying black spots along the road. Results show varying levels of factor influence across the three major roads which suggests that different road safety measures must be applied to each road. Collision Type and Time of Day have been found to be significant variables for all the three roads. Slope and U-turn slot locations were identified as an important factor contributing to the severity of crashes in EDSA, while minor roads intersections and carriageway width were deemed as significant factors in C5. In Commonwealth Avenue, carriageway width and location of U-turns were considered an important factor, in addition to horizontal curves and non-intersection locations. Notwithstanding the fact that the proposed methodology has been limited to a comparative study of three major roads, the findings have shown that the implementation of combined geostatistical techniques employed in this study shows promising perspective over conventional approaches in identifying crash reduction priority sites, as well as the influence of the associated spatiotemporal factors.
Thesis (Master of Science in Geomatics Engineering)--University of the Philippines Diliman
Keywords: Traffic accidents; Traffic safety